2020
DOI: 10.1093/jas/skaa072
|View full text |Cite
|
Sign up to set email alerts
|

Effect of post-ruminal guanidinoacetic acid supplementation on creatine synthesis and plasma homocysteine concentrations in cattle

Abstract: Creatine stores high-energy phosphate bonds in muscle, which is critical for muscle activity. In animals, creatine is synthesized in the liver from guanidinoacetic acid (GAA) with methylation by S-adenosylmethionine. Because methyl groups are used for the conversion of GAA to creatine, methyl group deficiency may occur as a result of GAA supplementation. With this study, the metabolic responses of cattle to post-ruminal supplementation of GAA were evaluated with and without methionine (Met) supplementation as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 38 publications
6
24
0
Order By: Relevance
“…Could there be a GAMT catalytic reaction that occurs in the body after dietary GAA supplementation? This may be evidenced from the serum metabolites HCY and CRE, given that HCY is the end-product of the methylation reaction on GAA (20,24) and CRE is the endproduct of CK catalyzing PCr in an energy releasing reaction (20,(40)(41)(42)(43)(44). In our study, we found that dietary GAA increased the HCY content of plasma, and CRE in both serum and LT muscles, indicating a substantial GAMT catalytic reaction and energy buffering effect.…”
Section: The Indicators Of Gaa On Methylguanidinoacetic and Energy Buffering Reactionssupporting
confidence: 54%
See 3 more Smart Citations
“…Could there be a GAMT catalytic reaction that occurs in the body after dietary GAA supplementation? This may be evidenced from the serum metabolites HCY and CRE, given that HCY is the end-product of the methylation reaction on GAA (20,24) and CRE is the endproduct of CK catalyzing PCr in an energy releasing reaction (20,(40)(41)(42)(43)(44). In our study, we found that dietary GAA increased the HCY content of plasma, and CRE in both serum and LT muscles, indicating a substantial GAMT catalytic reaction and energy buffering effect.…”
Section: The Indicators Of Gaa On Methylguanidinoacetic and Energy Buffering Reactionssupporting
confidence: 54%
“…At present, the existing literature (20,24,31,32) and our study revealed that GAA influenced beef growth and feed efficiency in bulls. In addition, GAA influenced body growth and feed efficiency in other ruminants (37)(38)(39), and also in poultry and other livestocks (1)(2)(3)(4)(5)(6)(7)(8)(9).…”
Section: The Indicators Of Gaa On Methylguanidinoacetic and Energy Buffering Reactionssupporting
confidence: 50%
See 2 more Smart Citations
“…Creatine is synthesized in the liver by GAA through S-adenosylmethionine methylation, and is essential for muscle activity. Phosphokinase catalyzes creatine to form high-energy creatine phosphate, and creatine phosphate is hydrolyzed to release energy and creatinine and phosphoric acid when energy is needed by the body [43] . We found that the serum phosphoric acid concentration was significantly lower in the group with meningoencephalitis compared with its concentration in the group without meningoencephalitis, which suggests the presence of energy homeostasis in neonatal sepsis with meningoencephalitis.…”
Section: Discussionmentioning
confidence: 99%